Makna dan Fungsi Tradisi Samman - Nor Hasan (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2017)
This article explains Samman as a tarekat established by Syekh Abdul Karim Al-Samman. First, as a tarekat, Samman functions as a way to reach closeness (taqarrub) to Allah SWT through strict procedures and requirement. The analysis of this article reveals that Samman is considered as a religious tradition maintained by the society in spite of dynamics and even decrease of its present followers. Second, as a tradition, Samman is considered as social wealth the existence of which is always protected and conserved. The efforts to conserve the tradition are realized through inheriting its construction and modification. For that reason, transmitting the tradition to the next generation is a must, as theimportant element of a tradition is its transmission from one generation to the next generation. It this is not realized, the tradition will vanish.